Blood Group Distribution and Its Relationship with Bleeding Time and Clotting Time: A Medical School Based Observational Study among Nepali, Indian and Sri Lankan Students - Roy, Bedanta; Banerjee, Indrajit; Sathian, Brijesh; Mondal, Monami; Saha, Chhanchu Gopal (Nepal Journal of Epidemiology, 2011)
Background Blood group, Bleeding Time and Clotting time are clinically useful tests, extensively used during blood transfusion, platelet disorders and a variety of forms of treatment in hospitals. The objective of our study was to assess the country wise distribution of blood groups and to compare the country wise bleeding time and clotting time with respect to blood group. Material and Methods This Observational Study has been performed at Manipal College of Medical Sciences, during the period of 1st May 2010 to 31st August–2011. The study was carried out on the undergraduate medical students of Basic sciences and included assessment of Bleeding time, Clotting time and Blood grouping by standard procedures. Results 261 medical students participated in the study. Among the Nepalese students, 30.5% had blood group A, 28.9% B, 5.5% AB and remaining 35.2% O. among the Indian students, 22.8% were blood group A, 45.7% B, 7.6% AB and 23.9% O. In Sri Lankan students, 22% had blood group A, 19.5% B, 4.9% AB, and 53.7% blood group O. Among Nepalese students, BT was higher in blood group A (163.85 seconds) as compared to Indians (154.29Sec) and Sri Lankans (133.33 sec). Nepalese students with AB blood group had higher BT (171.43 sec). Indian students with blood group A had comparatively higher clotting time (328.57 sec) followed by Nepali (276.15 sec) and then Sri Lankan students (270 sec). Girls are 4.432 times more prone for bleeding time greater than 4 minutes and 2.453 times for clotting time value above 6 minutes as compared to males. Conclusion Our study suggests that O blood group is predominant in Nepalese students while Blood group B was the most common blood group in the Indian students. We found higher BT and CT in females, which are more prominent in Indians, so this gender disparity is an additional risk factor for them. Health Ministries of respective countries have to improve the proper health care policies required for prevention and management of blood group diseases, bleeding time and clotting time related disorders like Hypoprothrombinemia and Thrombocytopenia. http://dx.doi.org/10.3126/nje.v1i4.5755 Nepal Journal of Epidemiology 2011;1(4):135-140